Mapping Child and Adolescent Mental Health Services and the Interface During Transition to Adult Services in Six Swiss Cantons - Kilicel, Deniz; De Crescenzo, Franco; Barbe, Remy; Edan, Anne; Curtis, Logos; Singh, Swaran; Micali, Nadia; Aubry, Jean-Michel; Mégevand, Jacqueline; Eliez, Stephan; Plessen, Kerstin Jessica; Armando, Marco (Frontiers in Psychiatry, 2022)
Rationale: Transition in psychiatry refers to the period where young people transit from Child and Adolescent Mental Health Services (CAMHS) to Adult Mental Health Services (AMHS). Discontinuity of care during this period is well documented but little is known about provisions and transition characteristics and policies across Switzerland. The aim of the present article is to describe the architecture of public mental health providers in Switzerland and compare it to EU countries. Method: Two mapping surveys, developed previously for European countries, were adapted and sent to cantonal experts: the adapted European CAMHS Mapping Questionnaire (ECM-Q) assessing the architecture and functioning of CAMHS and the adapted Standardized Assessment Tool for Mental Health Transition (SATMeHT) to map CAMHS-AMHS interface. Results: data was gathered from six cantons. Activity data and transition policies were comparable between Swiss regions and European countries. Work forces in Swiss CAMHS were comparable to European countries showing the most provisions and this in multiple areas. The percentage of young people below 19 who were in care was above 2% in every responding canton with a higher proportion of boys than girls for patients <12 years of age. Transition occurred at the age of 18, civil majority, in each canton and between 0-24% (3/7) and 25-49% (4/7) of young people were expected to transition. One canton (1/7) benefitted from written guidelines, at the CAMHS level only, regarding transition but none had guidelines for mapping CAMHS/AMHS interface even at the regional level. Conclusion: Despite the availability of resources and even if the possibilities of access to care are on average higher than in many European countries, issues regarding transition remain comparable in six Swiss cantons when compared to Europe. Meaning that beyond resources, it is really the coordination between services that needs to be worked on. Importantly, implementing those changes would not require investing financial resources but rather working on the coordination between existing teams.